Mathematical modelling and simulation of Protein Denaturation during Heat Treatment of Dairy Fluids - Tham, Heng Jin; Teo, Jason Tze Wi; Chu, Chi Ming (Universiti Malaysia Sabah, 2010)
Fouling has been a problem since the invention of heat exchanger. The presence of such deposits on heater surface can reduce the efficiency of the heater, which leads to plant shut down and subsequently loss of production. Fouling in the dairy industry is the most severe as daily cleaning of heat exchangers is often required, compared to other industries which only need yearly cleaning. Dairy fouling is caused by the thermal denaturation of betalactoglobulin at temperatures above 70oe. Therefore, this work was carried out to help the understanding of how transport phenomena in a heater affects the protein denaturation process. Modelling of the concentration of the native protein, denatured protein and aggregated protein during heat treatment of dairy product was successfully performed using finite element computational method. Based on the simulated concentration prOfiles, it is clear that native protein is not the contributor to fouling. It was also found that aggregated protein solely cannot be the main foulant. However, there is also possibility where depoSition is caused by both denature and aggregated proteins, but it is more complicated to predict the deposition pattern unless the ratio of the two depositing proteins involved is known through experiment. Experiments were also carried out to validate the simulation work, however, due to the raw materials used, results were found to be inconsistence.